Metodologi dan Teoretisasi Politik Islam - Sulthon (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
The main purpose of this research is to suggest that theoritically there is no specific and standard methodology to be used in the study of fiqh (Islamic jurisprudence) siyasah. It is because fiqh siyasah is more a part of a social science, where the methodology that might be used always changes and grows. As a part of fiqh, the study of fiqh siyasah needs to accommodate various methods of ijtihad as in the science of fiqh in general, such as qiyas, istihsan, istishab, maslaha mursalah, 'urf, and others. The study of fiqh siyasah can also use the five approaches such as philosophical, legal, empirical, bureaucracy, and ethics approach. Because the study of fiqh is quite complex and dynamic, then in the assessment and development of which need to be equipped with supporting sciences, such as sociology, anthropology, history, political science, economics, and others.The two fundamental questions to be answered in this research are; what is the methodology and approach of the Islamic political studies / fiqh siyasah and what are its characteristics. The method used in this research is descriptive and historical method. Descriptive method is used to describe a systematic, factual and accurate as well as the characteristics of the population in a particular region. While the historical method is used to reconstruct the past systematically and objectively by collecting, assessing, verifying, and synthesizing evidence to establish facts and to reach a strong conclusion